Food packaging : principles and practice - Robertson, Gordon L., 1946- (CRC Press, 2013)
"Food Packaging: Principles and Practice, Third Edition presents a comprehensive and accessible discussion of food packaging principles and their applications. Integrating concepts from chemistry, microbiology and engineering, it continues in the tradition of its bestselling predecessors and has been completely revised to include new, updated, and expanded content and provide a detailed overview of contemporary food packaging technologies. Features: Covers the packaging requirements of all major food groupsIncludes new chapters on food packaging closures and sealing systems, as well as optical, mechanical, and barrier properties of thermoplastic polymersProvides the latest information on new and active packaging technologiesOffers guidance on the design and analysis of shelf life experiments and the shelf life estimation of foodsDiscusses the latest details on food contact materials including those of public interest such as BPA and phthalates in foodsDevotes extensive space to the discussion of edible, biobased and biodegradable food packaging materials An in-depth exploration of the field, Food Packaging: Principles and Practice includes all-new worked examples and reflects the latest research and future hot topics. Comprehensively researched with more than 1000 references and generously illustrated, this book will serve students and industry professionals, regardless of their level or background, as an outstanding learning and reference work for their professional preparation and practice"-- Provided by publisher.
Keywords: Food -- Packaging.; elektronické knihy; electronic books